Development an ovine myocardial infarction- induced heart failure model and characterisation of altered calcium homeostasis mechanisms. (14th October 2021) - Niort, B C; Pius, C; Marris, C; Dibb, K M; Eisner, D A; Trafford, A W
Abstract: Introduction: Ventricular arrhythmias (VA) and heart failure (HF) are the major complications following myocardial infarction (MI). In both conditions, there is a key role for perturbed calcium homeostasis of which the underlying mechanisms remain unclear. A preclinical model that faithfully presents most of the features of MI-induced HF has been lacking. The complexity of this syndrome means that animal modelling is difficult. As the hearts of large animals share many electrophysiological similarities to humans, ovine modelling of cardiac diseases could better reflect human pathologies than in small mammals. Question: Is it possible to develop a clinically relevant ovine model with moderate cardiac dysfunction following myocardial infarction? Methods: MI was induced in sheep by inflating an angioplasty balloon distal to the second diagonal branch of the left anterior descending artery for 90 min. Cardiac function was monitored for 20 weeks using electrocardiography (ECG), echocardiography, blood biochemical analysis, and subjective signs of cardiac deterioration (lethargy, dyspnoea, and cough). 20 weeks post-MI, the animals were humanely killed and single left ventricular myocytes were isolated from the infarct border zone. Changes in cellular electrophysiology and intracellular calcium concentration were monitored using whole-cell patch technique in voltage-clamp mode and the calcium sensitive fluorescent indicator Fura-2 (K5 salt). Results: By using minimally invasive procedures, we obtained a survival rate of 80% (n=15). During surgery, our data show clinical features of ischaemia, including changes in the ECG features (elevation of the ST and T segment, left bundle branch block and/or pathological Q waves) and elevation of the cardiac biomarker such as troponin I. Following MI, we observed a decline in ejection fraction (−25±3%, p<0.0001) and an increase in whole animal arrhythmias (incidence of VA 72 hours post-MI, ∼70%). On cardiac removal apico-septal transmural necrosis / scarring was evident. Importantly, the L-type calcium current (ICaL) was decreased in MI cells compared to healthy cells (−1.87±0.73 pA/pF, p<0.05), but isoprenaline had no effet on ICaL (0.48±1.2 pA/pF, p=0.70) in MI cells. Moreover, the amplitude of the systolic calcium transient (−0.33±0.1 F/F0, p<0.05) and the sarcoplasmic reticulum calcium content (−23±7 μmol/L, p<0.01) were also decreased. The shortening velocity of the sarcomere was also decreased in MI cells (−0.55±0.18 μm/s, p<0.01). Conclusion: We successfully established an ovine MI model using minimally invasive procedure which displays a moderately impaired cardiac function, reduced contractility, and pro-arrhythmic electrophysiological remodelling. Future analysis will examine the role of the L-type calcium channel with respect to the excitation-contraction coupling process and myocyte contractility and how we can improve therapeutic strategies towards VA and HF. FUNDunding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): British Heart Foundation